ADDRESSING THE FACTORS INVOLVING IN THE ENDANGERMENT OF INDIGENIOUS LANGUAGES - Imama Sabir Rao; Rizvi Syed Sanober; Mehboob Ali Golo; Sonal Khan Maitlo (International Journal of Contemporary Issues in Social Sciences, 2023)
This research primed not only to divulge the factors involving in language endangerment, but also addressing these factors to solve the problem and preserve indigenous languages in the future. No community want to see their language in danger because with the death of a language the entire history perishes; but there are some factors which are leading to Pakistani indigenous languages to endangerment. The researchers explored and addressed these factors through this valuable research to solve this problem; to fulfill this purpose they face to face meet 360 participants and asked them seventeen close-ended questions and one open-ended question to find the answer of the both research questions. The purpose of this survey was to compose data to solve the problem investigated. The composed data was later analyzed by using “Statistical Package of Social Sciences” (SPSS); and analyzed data was presented in the tables and figures. Findings of this research indicated that mainstream of the research participants agreed that communication barriers, traveling, tourism, trends of language mixing, marriages and migrations are leading indigenous languages to the verge of danger. The processes of endangerment can be reverse able by giving special focus from its speakers. In the end researchers give some recommendations to preserve and restore these languages.